Characterizing the impact of pyrite addition on the efficiency of Fe0/H2O systems - Rui Hu (Nature Portfolio, 2021)
Abstract The role of pyrite (FeS2) in the process of water treatment using metallic iron (Fe0) was investigated. FeS2 was used as a pH-shifting agent while methylene blue (MB) and methyl orange (MO) were used as an indicator of reactivity and model contaminant, respectively. The effect of the final pH value on the extent of MB discoloration was characterized using 5 g L−1 of a Fe0 specimen. pH variation was achieved by adding 0 to 30 g L−1 of FeS2. Quiescent batch experiments with Fe0/FeS2/sand systems (sand loading: 25 g L−1) and 20 mL of MB were performed for 41 days. Final pH values varied from 3.3 to 7.0. Results demonstrated that MB discoloration is only quantitative when the final pH value was larger than 4.5 and that adsorption and co-precipitation are the fundamental mechanisms of decontamination in Fe0/H2O systems. Such mechanisms are consistent with the effects of the pH value on the decontamination process.